A multilayer thin-film screen-printed triboelectric nanogenerator - Hong, Daewoong; Choi, Young Man; Jang, Yunseok; Jeong, Jaehwa (International Journal of Energy Research, 2018)
In this study, we developed a multilayer thin-film triboelectric nanogenerator (MT-TENG) that incorporates a honeycomb-patterned spacer fabricated via screen printing by using ultraviolet curable ink. The printed spacer, a thin polymer layer, and thin metal electrodes enable the formation of a single thin-film structure. When force is applied to the thin-film TENG, the honeycomb-patterned spacer helps the polymer layer deform elastically through the opening of the pattern and contact the electrode. We implemented an MT-TENG by stacking 3 30 mm × 30 mm × 1.4 mm TENG layers electrically connected in parallel. The electrical performances of the manufactured MT-TENG with respect to the open-circuit voltage and short-circuit current were 11.45 V and 4.46 μA, respectively. The instantaneous output power density was 10.56 μW/cm3 (13.30 μW). In addition, an MT-TENG shoe insole was fabricated to harvest energy from human walking. We demonstrated that the fabricated shoe insole could light up 9 commercial green light-emitting diodes during walking to have an open-circuit voltage of about 20 V.
Keywords: Electrical performance; Green light emitting diodes; Multi-layer thin film; Nanogenerator; Output power density; Thin polymer layers; Thin-film structure; Ultraviolet curable; multilayer; screen printing; thin film; triboelectric nanogenerator